The key factors driving successful improvement in primary care : a mixed methods investigation of the determinants of quality improvement success in Aotearoa New Zealand : a thesis with publication presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Palmerston North, Aotearoa New Zealand - Cullen, Jane (Massey University, 2023)
Primary care is where the population receives most of their health care and where successful quality improvement (QI) can have the biggest impact on health, wellbeing, equity, and health system performance. A better understanding of the factors that influence QI in primary care is urgently needed to support a high-performing primary healthcare system. Most prior studies into the determinants of effective QI have focused on secondary care organisations and large-scale collaborative efforts. Primary care services such as general practice present a different set of challenges. Various key contextual factors have been identified in the literature, but few studies explain how they relate to each other and QI success. This study sought to answer the following questions: 1. What are the contextual factors influencing primary care improvement interventions? 2. How do the contextual factors, improvement content (topic and planned changes) and the implementation process influence each other and the improvement outcomes in primary care? 3. How applicable for primary care assessment is the Model for Understanding Success in Quality (MUSIQ), a tool for assessing modifiable contextual factors developed in secondary care? This research was an explanatory sequential mixed methods study based in the Aotearoa, New Zealand (NZ) primary care setting of general practice and Primary Health Organisations (PHOs). Amulti-case mixed methods approach was followed in the first stage. Mainly qualitative data were collected from primary care interviews guided by the Consolidated Framework for Implementation Research (CFIR). This was compared with quantitative data from the MUSIQ survey. The second stage consisted of a national survey where emerging theory was tested by partial least squares structural equation modelling (PLS-SEM). The findings revealed that most teams did not use formal QI methods, instead relying on their people-centred relationship skills and networks to drive QI via distributed leadership. Teams were intrinsically motivated by community and patient need and drew on strengths developed within the complexity and uncertainty of the primary care settings to drive QI. The collaborative skills which are increasingly required in the modern primary care setting support the shared social processes of sensemaking for enacting change. The key success factors driving QI in primary care are identified and how they relate to each other explained. A primary care adaptation of MUSIQ has been proposed that may aid improvement practitioners and researchers to assess primary care contexts. The key strengths should be developed and supported across primary care services and capability, capacity and resources supported centrally to increase the ability of primary care to improve services more easily and effectively.
Keywords: Primary health care; Health services administration; Medical care; Quality control; Total quality management; New Zealand; quality improvement; implementation; case study; partial least squares structural equation modeling; distributed leadership; general practice; network relationships; sensemaking; learning climate; 350715 Quality management; 401006 Systems engineering